Property Principles For MSMe Business Actors In Sail District, Pekanbaru City - Triana, Yeni; Nathassa Winstar, Yelia (Green Publisher, 2022)
The purpose of this community service is to analyze the understanding of business actors on the principle of propriety in running their business. In the Tugu Keris MSMe business group in Sail District, Pekanbaru City, in terms of the legal consequences that arise, they do not implement the principle of propriety in the perspective of business law. The output target is to increase the understanding of business actors towards the principle of propriety in establishing this partnership relationship, which is very important in the business world towards business competition to increase competitiveness and achieve profits, in particular, and, so the follow-up of the results of this service, may be useful for the service team and external parties related to small and medium enterprises regarding this decency principle are in the form of lecture study material articles for students and allow at the same time to do community service. The method of implementation is the nature of this service, namely lectures and questions and answers with participants. In the discussion of service, it was found that the problems faced by these business actors, it is necessary to solve the problem by providing a clear picture to the partners, because they have very little knowledge of the principle of propriety in establishing partnership relationships and the legal consequences that arise, therefore it is necessary to further legal counseling. Some of the findings in this service are used as material for improving the implementation of the utilization of the principle of propriety, to improve the community of business actors. The outputs produced are according to the activity plan for the proposer in the form of scientific articles, and learning study materials for students.